FAKTOR FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA PRODI S-1 AKUNTANSI ITB –AAS SURAKARTA UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI - Sri Laksmi Pardanawati (ITB AAS INDONESIA, 2021)
S1 Accounting Study Program students need to take additional Accounting Professional Education, but this is still a minimal number of public accountants at this time. This study aims to provide evidence about the influence of quality motivation, career motivation, economic motivation and achievement motivation on student interest in taking professional accounting education (PPA). Data collection techniques are carried out by providing a set of questions given to respondents, the data is a number of answers to a statement that includes the profile of the respondent and the variables to be studied, while the statistical test in this study uses multiple linear regression analysis with a significant level of 5%. The F test results (Simultaneous test results) concluded that Quality Motivation, Career Motivation, Economic Motivation and Achievement Motivation had a simultaneous influence on the interest in Accounting Profession Education. While the results of the t test (partial test) concluded that quality motivation, economic motivation and achievement motivation had no effect on student interest in taking accounting profession education, while krier motivation had an effect on student interest in taking accounting profession education and the value of the coefficient of determination Adjusted R Square was 0.348. This means that 34.8% of interest in participating in PPA can be explained by the four independent variables, namely quality motivation, career motivation, economic motivation and achievement motivation. Meanwhile, the other 62.2% were influenced by other variables which were not examined in this study.